Caregiver involvement in managing medications among older adults with multiple chronic conditions. Issue 10 (18th June 2021) - O'Conor, Rachel; Eifler, Morgan; Russell, Andrea M.; Opsasnick, Lauren; Arvanitis, Marina; Pack, Allison; Curtis, Laura; Benavente, Julia Yoshino; Wolf, Michael S.
Abstract: Objective: We sought to characterize caregiver medication assistance for older adults with multiple chronic conditions. Design: Semi‐structured qualitative interviews. Setting: Community and academic‐affiliated primary care practices. Participants: A total of 25 caregivers to older adults participating in an ongoing cohort study with ≥3 chronic conditions. Measurements: A semi‐structured interview guide, informed by the Medication Self‐Management model, aimed to understand health‐related and medication‐specific assistance caregivers provided. Results: Three typologies of caregiver assistance with medications emerged: Actively Involved, Peripherally Involved, and Not Involved. A total of 10 caregivers were Actively Involved, which was defined as when the caregiver perceived a need for and offered assistance, and the patient accepted the assistance. Peripherally Involved ( n  = 6) was defined as when the caregiver perceived a need and offered assistance; however, the patient rejected this assistance, yet relied on the caregiver as a backup in managing his or her medications. To combat resistance from the patient, caregivers in this typology disguised assistance and deployed workaround strategies to monitor medication‐taking behaviors to ensure safety. Lastly, nine caregivers were classified as Not Involved, defined as when the caregiver did not perceive a need to offer assistance with medications, and the patient managed his or her medicines independently. A strong preference toward autonomy in medication management was shared across all three typologies. Conclusion: These findings suggest that caregivers value independent medication management by their care recipient, up until safety is seriously questioned. Clinicians should not assume caregivers are actively and consistently involved in older adults' medication management; instead, they should initiate conversations with patients and caregivers to better understand and facilitate co‐management responsibilities, especially among those whose assistance is rejected by older adults.